The Role of K-Ras and PI3Kcb Expression in Oral Squamous Cell Carcinoma (Mustansiria Dental Journal, 2018)
Background: Oral squamous cell carcinoma is an aggressive malignancy. It arisesfrom premalignant lesions followed by outgrowth of clonal cell populations withcumulative genetic alterations. Phosphoinositol 3-kinases are a family of relatedintracellular signal transducer enzymes capable of phosphorylating the 3 positionhydroxyl group of the inositol ring of phosphatidylinositol (PtdIns).Phosphatidylinositol-3-kinases involved in cellular functions such as cell growth,proliferation, differentiation, motility, survival and intracellular trafficking, whichin turn are involved in cancer. RAS is a signal transduction protein for manyimportant cellular processes such as cellular proliferation, differentiation, andsurvival by mediating the cell's response to extracellular stimulations. Kras, is aprotein within the RAS family, function in the same pathway of a Ras –Raf -Mek-Erk-map kinase pathway which plays a role in mediating cellular response to cellgrowth. Kras appears to be involved in signal transduction and cell cycleregulation. To dates there has been limited previous investigation of proteinexpression of both PI3Kcb and Kras in oral squamous cell carcinoma. This studywas performed to examin the expression of PI3Kcb and kras in oral squamous cellcarcinoma in comparison to normal oral mucosa and to correlate the expression ofboth markers with clinicopathological findings including tumor grade and stageand with each other.Materials and Methods: This study included 31 selected cases of oral squamous cellcarcinoma pro and retrospectively and 10 cases normal oral mucosa. PIK3cb andKras expression has been detected by immunohistochemistry.Results: Results of the present study revealed positive PI3Kcb and kras expression inall examined oral squamous cell carcinoma cases. Immunostaining results for kras& PI3kcb were detected as brown stain for cell membrane and cytoplasm in tumorcells while there was no expression of both markers in normal oral mucosa. Nosignificant correlation was observed between both markers and theclinicopathological finding of oral squamous cell carcinoma while highlysignificant positive correlation was observed between the two markers.Conclusion: The Present study provides additional evidence that Kras, and PIK3cbover expression are common in contribution to oral squamous cell carcinomatumorigenesis, and that PI3Kcb signaling network plays an important role in oralsquamous cell carcinoma and thus, pathway-specific therapies targeting these twopathways should be considered in the future treatment of oral squamous cellcarcinoma patients